'They just had such a sweet way of speaking': Constructed voices and prosodic styles in Kodiak Alutiiq. (July 2019) - Fine, Julia Coombs
Abstract: Research in sociocultural linguistics has increasingly focused on the interplay of prosodic style, interactional stance, and personahood. This analysis investigates the prosodic stylization of constructed dialogue in Kodiak Alutiiq, an endangered Aleut-Yupik-Inuit language. Conceptualizing prosodic styles as comprised of multiple variables, I analyze each speaker's average F0, F0 range, voice quality, speech rate, and intonation contour across excerpts of constructed dialogue and non-constructed dialogue speech. The results emphasize the importance of considering interactional stance in conjunction with personahood and of examining the interactions of prosodic variables. Furthermore, the results demonstrate the important role narrative has to play in language revitalization efforts. Highlights: Speakers of Kodiak Alutiiq make use of prosodic features to animate personae in constructed dialogue. 'Persona' may be unpacked as the conjunction of stance and social role. Prosodic features of constructed dialogue vary according to both the stance and the social role of the constructed speaker. The interaction between social roles and stances is most clearly identified by considering multiple prosodic features.